"You don't pay your bills you get no protection": A Trump effect on NATO members' military expenditures? - Konstantina Founta; Chrēstos Kollias; Panayiotis Tzeremes (Peace Economics, Peace Science and Public Policy (PEPS), 2025)
Dispensing with the customary courteous diplomatic language, much of the 47th President's rhetoric concerning the other NATO Allies echoes the valid US criticism that many of them freeride on the US protective defence umbrella without contributing their fair share to the costs of NATO's collective defence. "You don't pay your bills, you get no protection...", he is quoted saying in a pre-election speech while is his Davos 2025 address, he mentioned, referring to the 2% NATO guideline and the effect of his first presidential term, that "...most nations didn't pay until I came along". Using such statements as an impetus, the paper sets out to examine whether a Trump effect of his first presidency on NATO members' military spending is empirically traceable. Results reported herein seem to offer evidence in favor of a tentative Trump effect inference.
Keywords: 320; K-Means; MDS; military spending; NATO; structural breaks; Trump